Analysis of the impact of various risk factors on short-term and long-term outcomes in patients with COVID-19 on maintenance hemodialysis - V. N. Suchkov; O. А. Klitsenko; K. K. Urtaeva; D. D. Avdoshina (Журнал инфектологии)
Patients receiving renal replacement therapy (RRT) in the form of maintenance hemodialysis (MHD) belong to a group of particularly high risk of infection and the course of COVID-19. The new coronavirus infection also has a great impact on long-term outcomes.Materials and methods: A retrospective observational study included 510 patients on MHD, hospitalized from April 1, 2020 to April 01, 2021. The outcome of hospitalization was chosen as the primary endpoint of the study: discharge or 28day mortality. Death within 6 months after discharge and the development of complications related to COVID-19 during this period were considered as secondary endpoints. Data collection was carried out by analyzing electronic and archival medical records. Quantitative variables: age, duration of hospitalization, days in the intensive care unit, laboratory blood parameters: the level of D-Dimer, Glucose, Interleukin-6, Procalcitonin, Lymphocytes and Platelets, CRP, CPK, CPK-MB, LDH, Fibrinogen, Ferritin. Qualitative indicators: gender, ventilator, ARDS, the presence of diabetes, the presence of obesity, the presence of complications: cardiovascular, gastrointestinal, septic, macrothrombotic, stage of pneumonia. To identify statistically significant predictors of the risk of an event, the odds ratio (OR) method was used.Results: average age 57.8±14 years, men – 59.5%, average bed day 17.6±10.6 days. In concomitant diseases, diabetes mellitus was indicated in 24% of patients, obesity was registered in 4.3% of patients. Hospital mortality (28-day) in the total cohort of follow-up was 16.05%, in total with out-ofhospital mortality of 22%. Mortality in intensive care reached 62.7%, on ventilator more than 86%, with ARDS 94.3%. No statistical significance was revealed by gender and the presence of diabetes mellitus (DM) in concomitant diseases. When comparing short-term outcomes, the age groups over 65 differed statistically. The following laboratory blood parameters showed a significant difference (P<0.001): D-Dimer, Glucose, IL-6 lymphocytes, Leukocytes, Neutrophils, Platelets, LDH, Ferritin. The following odds ratios (OR) were obtained: ARDS (OR 143.78; 95% CI 33.4-616.2; p=0.0001), on ventilator (OR 57.96; 95% CI 23.1-144.5; p=0.0001), the presence of septic complications (OR 26.4; 95% CI 13.8-50; p=0.0001), the course of the disease is defined as severe (OR 25; 95% CI 12.9-48.2; p=0.0001), the course of the disease is defined as complicated (OR 11.6; 95% CI 6.8-19.7; p=0.0001), the presence of gastrointestinal complications (OR 6.5; 95% CI 2.28-18.4; p=0.0007), the presence of obesity (OR 2.57; 95% CI 1.0-6.5; p=0.039). Mortality of patients receiving two main treatment regimens T-1 and T-2 did not differ (15.8% vs 15.7%). Significant differences (p=0.0001) appeared when compared with the T-0 and T-4 schemes, in which mortality was recorded at 8.8% and 85.7%, respectively. When comparing long-term outcomes, the analysis did not reveal statistical significance by gender. The statistical difference was noted by age. Among laboratory indicators, the PCT level was higher in survivors with complications. A significant difference among all survivors and deceased (P<0.001) was shown by: D-Dimer, blood glucose level, IL-6, CRP. The highest OR was calculated for the following indicators: the presence of gastrointestinal complications (OR 7.7; 95% CI 1.0-57.7; p=0.03), the initial LDH blood level of 622 units /l (OR 4.7; 95% CI 1.63-13.63; p=0.0086), the course of the disease defined as complicated (OR 4.05; 95% 1.97-8.33; p=0.003), the course of the disease is defined as severe (OR 2.4; 95% CI 1.17-5.0; p=0.03).Conclusions: gastrointestinal complications had the greatest impact on unfavorable short-term and long-term outcomes in patients on programmed hemodialysis. In relation to such laboratory markers as Ferritin, CRH, LDH, threshold values of a significant increase in the chances characteristic of dialysis patients were obtained. During the first year of the epidemic, therapy remained largely supportive and aimed at preventing complications, the main isolated treatment regimens showed no significant differences in the impact on the outcomes of COVID-19.